Advances in Psoriasis Biological Agent - Nopriyati; Reza Mayasari (Arkus, 2019)
Biological agents are proteins that have pharmacological activity, derived from living materials, either from humans, animals, or microorganisms, and can be synthesized in large quantities with the help of genetic engineering techniques (recombinant DNA techniques). Biological agents are divided into three types: monoclonal antibodies in humanized, primatized, fully human, chimeric; cytokines or recombinant human cytokines growth factors; and 3) fusion proteins. The nomenclature for receptor fusion proteins and monoclonal antibodies follows the rules established by the International Nonproprietary Names of the World Health Organization (WHO). The suffix "-cept" is used as a code to identify a drug as a receptor molecule, and "-mab" is used as a code for a monoclonal antibody. The origin of the antibody is indicated by the code "-u-" for fully human origin (e.g., secukinumab). Antibodies derived from humans and mice are humanized, code named "-Zu-" (e.g., ixekizumab or chimeric, "-xi-" (eg, infliximab).